ROAD NETWORK SIMULATION MODEL ANALYSIS OF PAHLAWAN ROAD AREA WITH TRAFFIC MANAGEMENT AND ENGINEERING EFFORTS - Zein, Fikri Haikal; Muhammadun, Haris; Marleno, Risma (Transpublika Publisher, 2024)
During peak hour conditions, the traffic orderly area (KTL) in the existing Pahlawan Road area has not provided maximum results regarding performance and traffic order. The solution to the transportation problems that occur is to assess the performance of related sections and intersections and analyze the selection of traffic handling schemes to produce the most effective and efficient handling output. The purpose of this study is to determine the most optimal traffic engineering management recommendations for Pahlawan Road, Sidoarjo Regency. In data processing, researchers analyzed survey data, including the analysis of the traffic trip destination-origin matrix, vehicle free speed, vehicle behavior, and intersection control. The authors calibrated and validated the simulation model using the Vissim application, which represents the real situation in the field. Analysis of the traffic performance of the existing condition of the Pahlawan Road area road network revealed an average delay of 96.5 seconds, an average vehicle speed of 23.7 km/h, a total vehicle travel time of 1,691.6 hours, and a total vehicle delay of 725.2 hours, indicating poor road network performance. To improve the performance of the road network on the Pahlawan road section, the authors developed six road network simulation scenarios to derive the most optimal traffic engineering management recommendations for Pahlawan Road, Sidoarjo Regency.